Involvement of adenosine A1 receptor in electroacupuncture-mediated inhibition of astrocyte activation during neuropathic pain - Zhang, Mingxiao; Dai, Qinxue; Liang, Dongdong; Li, Dan; Chen, Sijia; Chen, Shuangdong; Han, Kunyuan; Huang, Luping; Wang, Junlu (Arquivos de Neuro-Psiquiatria, 2018)
Neuropathic pain is a chronic pain condition caused by damage or dysfunction of the central or peripheral nervous system. Electroacupuncture (EA) has an antinociceptive effect on neuropathic pain, which is partially due to inhibiting astrocyte activation in the spinal cord. We found that an intrathecal injection of 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), a selective adenosine A1 receptor antagonist, reversed the antinociceptive effects of EA in a chronic constriction injury-induced neuropathic pain model. The expression of GFAP in L4-L6 spinal cord was significantly upgraded, while DPCPX suppressed the effect of the EA-mediating inhibition of astrocyte activation, as well as wiping out the EA-induced suppression of cytokine content (TNF-α). These results indicated that the adenosine A1 receptor is involved in EA actions during neuropathic pain through suppressing astrocyte activation as well as TNF-α upregulation of EA, giving enlightenment to the mechanisms of acupuncture analgesia and development of therapeutic targets for neuropathic pain.
Keywords: Electroacupuncture; astrocytes; receptor, adenosine A1; cytokines, neuralgia